Psychological Empowerment dan Perilaku Inovatif: Peran Moderasi Work Engagement pada Karyawan Milenial Sektor Perbankan - Putri, Melisa Ariani; Meitisari, Nia (Jurnal Pustaka Aktiva (Pusat Akses Kajian Akuntansi, Manajemen, Investasi, dan Valuta), 2026)
Abstract The rapid advancement of digital transformation in the banking sector requires organizations to enhance employees' innovative behavior to maintain their competitive advantage. One of the factors believed to foster innovative behavior is psychological empowerment, while work engagement is expected to strengthen this relationship. This study aims to examine the effect of psychological empowerment on innovative behavior and to investigate the moderating role of work engagement among millennial employees in the banking sector in Palembang City. This research employed a quantitative approach using an explanatory research design. Data were collected through a questionnaire survey administered to 150 millennial banking employees selected using purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The findings indicate that psychological empowerment has a positive and significant effect on innovative behavior. Furthermore, work engagement also has a positive and significant effect on innovative behavior. The moderation analysis reveals that work engagement strengthens the positive relationship between psychological empowerment and innovative behavior. The study concludes that enhancing innovative behavior among millennial employees in the banking sector requires a combination of psychological empowerment and high levels of work engagement. These findings provide practical implications for banking management in designing human resource management strategies aimed at fostering employee innovation. Keywords: psychological empowerment, innovative behavior, work engagement, millennial employees, banking sector. Abstrak Perkembangan transformasi digital pada sektor perbankan menuntut organisasi untuk meningkatkan perilaku inovatif karyawan sebagai upaya mempertahankan daya saing. Salah satu faktor yang diyakini mampu mendorong perilaku inovatif adalah psychological empowerment, sementara work engagement diperkirakan dapat memperkuat hubungan tersebut. Penelitian ini bertujuan menganalisis pengaruh psychological empowerment terhadap perilaku inovatif serta menguji peran moderasi work engagement pada karyawan milenial sektor perbankan di Kota Palembang. Penelitian ini menggunakan pendekatan kuantitatif dengan desain explanatory research. Data dikumpulkan melalui penyebaran kuesioner kepada 150 karyawan milenial yang dipilih menggunakan teknik purposive sampling. Analisis data dilakukan menggunakan Partial Least Squares Structural Equation Modeling (PLS-SEM) dengan bantuan perangkat lunak SmartPLS 4. Hasil penelitian menunjukkan bahwa psychological empowerment berpengaruh positif dan signifikan terhadap perilaku inovatif. Selain itu, work engagement juga berpengaruh positif dan signifikan terhadap perilaku inovatif. Pengujian efek moderasi menunjukkan bahwa work engagement mampu memperkuat pengaruh psychological empowerment terhadap perilaku inovatif. Penelitian ini menyimpulkan bahwa peningkatan perilaku inovatif karyawan milenial sektor perbankan memerlukan kombinasi antara pemberdayaan psikologis dan keterikatan kerja yang tinggi. Temuan ini memberikan implikasi praktis bagi manajemen perbankan dalam merancang strategi pengelolaan sumber daya manusia yang berorientasi pada peningkatan inovasi. Kata kunci: psychological empowerment, perilaku inovatif, work engagement, karyawan milenial, sektor perbankan.